A New MAMLD1 Variant in an Infant With Microphallus and Hypospadias With Hormonal Pattern Suggesting Partial Hypogonadotropic Hypogonadism—Case Report - Yeste, Diego; Aguilar-Riera, Cristina; Canestrino, Gennaro; Fernández-Alvarez, Paula; Clemente, María; Camats-Tarruella, Núria (Frontiers in Endocrinology, 2022)
MAMLD1 (X chromosome) is one of the recognized DSD-related genes. It is expressed in testis and ovaries, and seems to be involved in foetal sex development and in adult reproductive function, including testosterone biosynthesis. However, its exact role is still not clear. Over 40 genetic variants have been described, mainly in males and mostly associated with hypospadias. Although MAMLD1 has been shown to regulate expression of steroidogenic pathway, patients with MAMLD1 variants mostly show normal gonadal function and normal testosterone levels. Here we describe a patient (46,XY) with hypospadias and microphallus with low testosterone and DHT levels, with inappropriate low values of LH during minipuberty. This hormonal pattern, was suggestive of partial hypogonadotropic hypogonadism. A stimulation test with hCG (4 months) showed no significant increase in both testosterone and DHT concentrations. At 5 months of age he was treated with intramuscular testosterone and penis length increased to 3.5 cm. The treatment was stopped at 6 months of age. Our gonadal-function massive-sequencing panel detected a non-previously reported nonsense variant in the MAMLD1 gene (c.1738C>T:p.Gln580Ter), which was classified as pathogenic. This MAMLD1 variant, predicting a truncated protein, could justify his genital phenotype. His hormonal profile (low testosterone, DHT and LH concentrations) together with no significant increase of testosterone and DHT plasma concentrations (hCG test) highlight the potential role of this gene in the biosynthesis of testosterone during the fetal stage and minipuberty of the infant. Besides, LH values may suggest an implication of MAMLD1 in LH axis or a possible oligogenesis. It is the first time that a decrease in DHT has been described in a patient with an abnormal MAMLD1.